NATURE OF CARBONATE KARST ACTIVATION AND ITS ECOLOGICAL CONSEQUENCES: (on example of the complex investigations in the territory of Ras Al Ayn City, SAR) (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
Karst as a dangerous engineering-geological process is especially disastrous for civil, industrial and hydrotechnical constructions. The article is discussing the results of engineering-geological, hydrogeological and geophysical complex investigations that were carried out in the northern part of Syria: in the territory of Ras Al Ayn City. Karst processes have been activated last few years in this territory mainly because of human activities. A number of target maps are drawn for case study area including zoning map of the karst risk, according to that map the city territory is divided into 3 parcels. Necessary engineering measures are proposed for ecological remediation of the studied area.
Keywords: karst process; karst subsidence and failures; karst risk map; Ras Al Ayn City